Determination of reducing carbohydrates in natural honey samples by optical micrometry method - Ivan S. Shchemelev; Danil S. Khasanov; Maria A. Smirnova; Alexander V. Ivanov; Nikolay B. Ferapontov; Mikhail G. Tokmachev (Chimica Techno Acta)
The present article deals with the determination of the total amount of glucose and fructose in natural honey samples by the optical micrometry (OM) method. (Poly)vinyl alcohol spherical granules impregnated with a 0.05 mol/l borax solution were chosen as a sensitive element. It was shown that the formation of chelate esters of boron with polymer and carbohydrates is a pH-dependent process, and that the pH range 8.5–10.0 is the most appropriate for quantifying the total amount of reducing carbohydrates because glucose and fructose are undiscriminated. The impregnated polymer is not sensitive to the sucrose presence in the solution due to the absence of cis-diol fragments in it. Subsequently, the OM method was tested in the analysis of natural honey samples. The relative standart deviation in the case of OM method is less than 6%, and the results are similar to those obtained by the iodometric titration method. This makes the OM method suitable for laboratory-scale applications.